Critical Review of Gaps in the Diagnosis and Management of Drug-Induced Liver Injury Associated with Severe Cutaneous Adverse Reactions - Villanueva-Paz, Marina; Niu, Hao; Segovia-Zafra, Antonio; Medina-Cáliz, Inmaculada; Sanabria-Cabrera, Judith Adriana; Lucena-González, María Isabel; Andrade-Bellido, Raúl Jesús; Álvarez-Álvarez, Ismael (MDPI, 2021)
Drug-induced liver injury (DILI) encompasses the unexpected damage that drugs can cause to the liver. DILI may develop in the context of an immunoallergic syndrome with cutaneous manifes- tations, which are sometimes severe (SCARs). Nevirapine, allopurinol, anti-epileptics, sulfonamides, and antibiotics are the most frequent culprit drugs for DILI associated with SCARs. Interestingly, alleles HLA-B*58:01 and HLA-A*31:01 are associated with both adverse reactions. However, there is no consensus about the criteria used for the characterization of liver injury in this context, and the different thresholds for DILI definition make it difficult to gain insight into this complex disorder. Moreover, current limitations when evaluating causality in patients with DILI associated with SCARs are related to the plethora of causality assessment methods and the lack of consensual complementary tools. Finally, the management of this condition encompasses the treatment of liver and skin injury. Although the use of immunomodulant agents is accepted for SCARs, their role in treating liver injury remains controversial. Further randomized clinical trials are needed to test their efficacy and safety to address this complex entity. Therefore, this review aims to identify the current gaps in the definition, diagnosis, prognosis, and management of DILI associated with SCARs, proposing different strategies to fill in these gaps.
Keywords: Ensayo clínico; Hígado -- Enfermedades; Hipersensibilidad; Lesión hepática inducida por fármacos; Reacciones adversas cutáneas graves; Evaluación de causalidad; Diagnóstico; Respuesta inmune